Approach to impaired corollary discharge in patients with schizophrenia: An analysis of self-induced somatosensory evoked potentials and fields - Yagyu, Kazuyori; Toyomaki, Atsuhito; Hashimoto, Naoki; Shiraishi, Hideaki; Kusumi, Ichiro; Murohashi, Harumitsu (Frontiers in Psychology, 2022)
Background: Difficulty in distinguishing between self-generated actions and those generated by others is a core feature of schizophrenia. This is thought to be underpinned by failure of corollary discharge. However, few studies have investigated these events using somatosensory evoked potentials (SEPs) and somatosensory evoked magnetic fields (SEFs). Methods: The study included 15 right-handed patients with schizophrenia and 16 healthy controls. SEP and SEF were elicited by electrical stimuli to the left median nerve at intervals of 1–3 s. In the external condition, stimuli were externally induced by a machine. In the self condition, stimuli were induced by tapping the participants’ own right index finger. Peak amplitude at C4’ in SEP and root mean square in 10 channels on the right primary somatosensory area in SEF were analyzed. Results: Although there was a significant main effect of condition at N20m, and a significant main effect of condition and group at P30m, no significant interactions of condition and group were found in either N20m or P30m. Post-hoc Wilcoxon tests revealed that the peak value of P30m in the external condition was significantly higher than that in the self condition in the healthy control group only. In addition, there was a significant positive correlation between the peak value of P30m in the self condition and a positive symptom score. Conclusion: In the current study, we did not find abnormalities of corollary discharge in primary sensory areas in patients with schizophrenia. Further investigations with more cases may reveal the possibility of corollary discharge disturbance in the primary sensory cortex.